Efficacy and safety of acupuncture as an adjuvant treatment for acute pancreatitis: a protocol of systematic review and meta-analysis - Jingbo Zhai; Yan Li; Chen Zhao; Kai Zhang; Chengyu Li; Chao Gao; Qilin Tang (BMJ Open)
Introduction Acupuncture may be effective for acute pancreatitis (AP). This systematic review aims to assess the efficacy and safety of acupuncture as an adjuvant treatment for AP.Methods and analysis We will search PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, Web of Science, China National Knowledge Infrastructure, Wan Fang Data and Chinese Science Journal Database from inception to 30 June 2019 to identify any eligible study. Only randomised controlled trials will be included. The selection of studies, data extraction and management will be completed by two reviewers independently. The primary outcomes include the overall response rate, mortality during the treatment, the proportion of patients with severe acute pancreatitis transferred to the intensive care unit or scheduled for surgery, gastrointestinal function and the acute physiology and chronic health evaluation II scores. The secondary outcomes include visual analogue scale, the use of analgesics, the recovery time of blood amylase becoming normal, tumour necrosis factor α counts, IL-6 counts, IL-10 counts, length of hospital stay and adverse events related to acupuncture (such as fainting, nausea, haematoma and local infection). Review Manager V.5.3 software will be used for statistical analyses. The risk of bias of included studies will be assessed by the Cochrane ‘risk of bias’ tool.Ethics and dissemination This study will not involve personal information. The ethical approval will not be required. The results will be published in a peer-reviewed journal.Trial registration number CRD42018115099